2022
DOI: 10.4240/wjgs.v14.i7.670
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comorbid renal dysfunction in patients with hepatocellular carcinoma on long-term outcomes after curative resection

Abstract: BACKGROUND Hepatocellular carcinoma (HCC) is one of the most common malignancies worldwide. However, the number of patients with chronic kidney disease (CKD) is on the rise because of the increase in lifestyle-related diseases. AIM To establish a tailored management strategy for HCC patients, we evaluated the impact of comorbid renal dysfunction (RD), as stratified by using the estimated glomerular filtration rate (EGFR), and assessed the oncologic validity of hepatecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Even if HCC patients complicated with renal failure have a normal platelet count, increased capillary fragility and the disturbance of blood coagulation may result in post-operative hemorrhage. Therefore, close attention to severe CKD is needed to prevent post-operative bleeding [44,45].…”
Section: Comorbidity Of Renal Failurementioning
confidence: 99%
“…Even if HCC patients complicated with renal failure have a normal platelet count, increased capillary fragility and the disturbance of blood coagulation may result in post-operative hemorrhage. Therefore, close attention to severe CKD is needed to prevent post-operative bleeding [44,45].…”
Section: Comorbidity Of Renal Failurementioning
confidence: 99%
“…Currently, there are no long-term data regarding HCC risk for the newer first-line HBV medication TAF, though some studies have demonstrated that switching from ETV or TDF to TAF can lead to further increase in virologic response, while preserving renal function. [28][29][30][31][32][33][34][35] Currently, professional society guidelines recommend antiviral treatment for patients without cirrhosis with elevated HBV DNA (≥2000-20,000 IU/mL) and elevated alanine aminotransferase (ALT) levels or fibrosis stage 2 or higher (Table 1) 16,17,[36][37][38] . For patients with cirrhosis especially those with decompensated cirrhosis, antiviral therapy is generally recommended for patients with any level of detectable HBV DNA and irrespective of ALT levels.…”
mentioning
confidence: 99%